2012
DOI: 10.1128/mcb.00438-12
|View full text |Cite|
|
Sign up to set email alerts
|

Intermolecular Binding between TIFA-FHA and TIFA-pT Mediates Tumor Necrosis Factor Alpha Stimulation and NF-κB Activation

Abstract: T he forkhead-associated (FHA) domain, discovered in 1995 (10) and first suggested to bind phosphoproteins in 1998 (24), is known to specifically recognize phosphothreonine (pT) to exert its function (5,20). Although the sequence homology among different FHA-containing proteins is relatively low, the structural architecture of FHA domains is highly conserved. It contains a six-stranded ␤-sheet and another five-stranded ␤-sheet, forming a ␤-sandwich. The FHA-pT binding has been shown to regulate diverse biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 31 publications
6
54
0
Order By: Relevance
“…Our previous study uncovered that this functional event requires the phospho-threonine 9 (pThr9)-directed oligomerization of TIFA dimer upon TNFa stimulation (21). In the current study, we further identified Aurora A as an essential kinase for TIFA phosphorylation at Thr9 and showed that TIFA mediates the Aurora A-dependent NF-kB signaling pathway.…”
Section: Introductionmentioning
confidence: 56%
See 4 more Smart Citations
“…Our previous study uncovered that this functional event requires the phospho-threonine 9 (pThr9)-directed oligomerization of TIFA dimer upon TNFa stimulation (21). In the current study, we further identified Aurora A as an essential kinase for TIFA phosphorylation at Thr9 and showed that TIFA mediates the Aurora A-dependent NF-kB signaling pathway.…”
Section: Introductionmentioning
confidence: 56%
“…All resulting STR profiles were matched with known ATCC fingerprints (www.ATCC.org). Maintenance of respective cell lines followed our previous protocols (21)(22)(23). 293T and HeLa cells were maintained in DMEM(Gibco).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations